2009
DOI: 10.1055/s-0029-1214712
|View full text |Cite
|
Sign up to set email alerts
|

Interventional endoscopic ultrasound-guided cholangiography: long-term experience of an emerging alternative to percutaneous transhepatic cholangiography

Abstract: IEUC offers a feasible alternative to PTC in patients with obstructive jaundice in whom ERC has failed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
78
3
8

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(90 citation statements)
references
References 13 publications
1
78
3
8
Order By: Relevance
“…35 had biliary obstruction due to malignancy and 14 had a benign etiology. The overall success rate of IEUC was 84 % with an overall complication rate of 16 % [44] . IEUC has possible advantages over PTC in patient comfort, lower morbidity and offers a possible alternative to patients with obstructive jaundice in whom ERCP has failed.…”
Section: Endoscopic Ultrasonagraphy Guided Cholangiographymentioning
confidence: 94%
“…35 had biliary obstruction due to malignancy and 14 had a benign etiology. The overall success rate of IEUC was 84 % with an overall complication rate of 16 % [44] . IEUC has possible advantages over PTC in patient comfort, lower morbidity and offers a possible alternative to patients with obstructive jaundice in whom ERCP has failed.…”
Section: Endoscopic Ultrasonagraphy Guided Cholangiographymentioning
confidence: 94%
“…Multivariate analysis identified the transhepatic route as the only independent factor associated with procedure risk, with the study concluding that the preferred route is extrahepatic for transluminal and rendezvous stent placement, when both intra-and extrahepatic approaches are feasible [284]. Studies have found lower success rates with the intrahepatic compared with the extrahepatic approach due to a failure to pass a guidewire through the intrahepatic system and stricture [271,278]. In a separate study 13 % of intrahepatic approaches were converted to the extrahepatic access route [271].…”
Section: Guidelines E86mentioning
confidence: 99%
“…Studies have found lower success rates with the intrahepatic compared with the extrahepatic approach due to a failure to pass a guidewire through the intrahepatic system and stricture [271,278]. In a separate study 13 % of intrahepatic approaches were converted to the extrahepatic access route [271]. A rarely used approach with a pooled success rate of 77 % (30/39 cases) is the transhepatic access followed by an intraductal anterograde drainage or dilatation of strictures of the bile duct, papilla or biliodigestive anastomoses [278 -281], which may then be combined with transluminal intrahepatic drainage procedures [282].…”
Section: Guidelines E86mentioning
confidence: 99%
“…In failed ERCP-bile duct/pancreatic duct cannulations, EUS has been successful in performing cholangiography or pancreatography. Maranki et al have shown EUS having an overall success rate of 84% with 16% complication rate and no procedure-related mortality from a series of 49 patients with failed ERCP [34]. Clinical trials are being performed to study the role of various antitumor agents (being injected, EUS-guided) in unresectable pancreatic cancer [35][36][37].…”
Section: Therapeutic Indication For Eusmentioning
confidence: 99%